Recording application for Ettawa-Crossed goat herd improvement: a case study in Samigaluh, Kulon Progo District - Maharani, Dyah (2014)
The program of Ettawa-crossed goat recording system has been carried out in Samigaluh, Kulon Progo District to develop Village Breeding Center (VBC). Initially, a goat herd namely “Menoreh Maju” Located in Kayu Gede, Samigaluh was a pilot program. Twelve farmers and total 74 heads of goat were involved in the program. The recording system program was initiated with the purpose of achieving genetic improvement in VBC as superior kid goat producers. Community mentoring method was used to achieve the goal of the program. The individual data have been recorded and made up an individual card. The goat characteristics were identified based on animal herd age and sex, birth and weaning data, and milk production. Those data were recorded in farmer’s log book. The leader of goat farmer association collected and evaluated the recording data in every month on their regular meeting. The farmers actively participated in the program socialization. However, as the program implemented, it was soom realized that some farmers would not participated in the program due to their goat have been sold for economically reason. In conclusion, the mentoring of the program is still needed for the better future in herd improvement.